Multicentric evaluation of sensitivity of eight commercial anti-SARS-CoV-2 antibody assays and their correlation to virus neutralization titers in seropositive subjects - Fajfr, Miroslav; Pajer, Petr; Ruzek, Daniel; Sleha, Radek; Janovska, Sylva; Bohonek, Milos; Kabickova, Hana; Kubicková, Pavla; Stefanik, Michal; Strakova, Petra; Bostik, Pavel (Scientific reports, 2024)
Diagnosis of SARS-CoV-2 virus is mainly based on direct detection. Determination of specific antibodies has been used mostly for epidemiological reasons. However, select immunoassays showed good correlation to plaque reduction virus neutralization test (PRNT) in smaller patient cohorts, which suggests their potential as predictors of virus neutralization titer. A total of 3,699 samples from Covid-19 patients were included in the multicentric study performed in the Czech Republic. Anti-SARS-CoV-2 antibody levels were evaluated by 8 commercial antibody assays. Simultaneously, PRNT evaluations were performed with the SARS-CoV-2 B.1.258 variant. All immunoassays showed an overall high true positive diagnostic value ranging from 79.17 to 98.04%. Several commercial EIA methods showed highly positive correlation between the assay results and PRNT levels, e.g., Liaison CoV-2 TrimericS IgG DiaSorin (Spearman r = 0.8833; Architect SASRS-CoV-2 IgG Abbott (r = 0.7298); NovaLisa SARS-CoV-2 IgG NovaTec (r = 0.7103) and Anti-SARS-CoV-2 ELISA IgG Euroimmun (r = 0.7094). While this correlation was less positive for other assays, those, conversely, presented higher true positive values. For most immunoassays, the positive percent agreement of the results was ≥ 95% in sera exhibiting PRNT levels of 1:80 and higher. The assays tested have shown variable correlation to PRNT. Those possessing high positive predictive values serve well as qualitative tests, while others can be utilised as quantitative tests highly predictive of neutralization antibody levels.
Keywords: Neutralization Tests; protilátky virové; COVID-19; Sensitivity and Specificity; senzitivita a specificita; Serologic Tests; neutralizující protilátky; sérologické testy; Humans; Antibodies, Viral; SARS-CoV-2; neutralizační testy; lidé; Immunoglobulin G; Antibodies, Neutralizing; imunoglobulin G